From Revision to Practice: Key Changes in the Revised 2025 Scope and Standards of Practice for Registered Dietitian Nutritionists in Oncology Nutrition - Laura Kelly; Mridul Datta; Anna Arthur; Michelle Strang; Karen Hui (Journal of the Academy of Nutrition and Dietetics, 2025)

From Revision to Practice: Key Changes in the Revised 2025 Scope and Standards of Practice for Registered Dietitian Nutritionists in Post-Acute and Long-Term Care Nutrition - Rena Zelig; Paula Ritter-Gooder; Carol J. Gilmore; Michelle Strang (Journal of the Academy of Nutrition and Dietetics, 2025)

Updated Terminology for the Nutrition and Dietetics Profession: A Comprehensive Revision to the Commission on Dietetic Registration’s Definition of Terms List - Chris Messenger; Nancy Walters; Anna Marie Rodriguez; Laura Gollins; ShLanda Rochel Burton; Lini Alappat; Rayna McCann; Michelle Strang; Dana Buelsing Sowards; Carol Gilmore; Karen Hui (Journal of the Academy of Nutrition and Dietetics, 2025)

Review of the techniques for estimating population size of Adélie penguins (Pygoscelis adeliae) - Alexandra J. Strang; Elissa Z. Cameron; Dean P. Anderson; Esme Robinson; Michelle A. LaRue (Polar Biology, 2025)
Monitoring of sentinel species provides insight into the ecosystems in which they live. In the Southern Ocean, penguins are one such indicator species, where only a limited number of colonies have been monitored extensively for decades around Antarctica. As the Southern Ocean warms and commercial fishing continues, the need for expansion of population monitoring has become paramount. Using Adélie penguins ( Pygoscelis adeliae ) as a model species, we reviewed methods to estimate colony size including ground and aerial (occupied and unoccupied aircraft) assessment and satellite imagery, with an aim of understanding costs and benefits of each method to inform their future use. Ground assessment includes physically taxing field counts of individuals or nests and was historically the only method used to count penguins in Antarctica. Aerial assessments via occupied and unoccupied aircraft have expanded the spatial extent of monitoring for remote and logistically challenging environments such as Antarctica. Combined with aerial assessment, the more recent use of very high-resolution satellite imagery (VHR) has further expanded Adélie penguin monitoring into previously inaccessible areas. Adélie penguin breeding colonies can be monitored using VHR imagery through the area of their guano stain as a proxy for the number of breeding pairs. Our review provides an overview of the monitoring techniques for Adélie penguins in Antarctica and provides direction for future use and development.

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)